Research on the Influence of Rotational Speed on the Noise of V-ribbed Belt Three-wheel Drive System - Xuecheng Zhang; Zhendong Jiang; Yaochen Shi; Tianxiang Zhao (Jixie chuandong)
In order to study the influence of speed on the noise level of the V-ribbed belt three-wheel drive system，taking the 6PK V-ribbed belt as an example，a noise test device for the three-wheel drive system of the V-ribbed belt is built based on the acoustic array principle，and the time-domain signal and noise sound pressure distribution cloud diagram of the sound pressure in the transmission system of three wheels at different speeds are obtained. As the rotation speed increases，the noise in the V-belt three-wheel drive system gradually increases. The low-frequency noise caused by the lateral vibration of the V-ribbed belt gradually increases with the increase of the speed. The increase in the lateral vibration noise of the V-ribbed belt is measured by the Doppler laser vibrometer is caused by the increase in the amplitude of the lateral vibration of the V-ribbed belt. It can be seen from the noise sound pressure cloud diagram that the high frequency friction noise caused by the friction between the V-ribbed belt and the pulley increases with the increase of the speed，when the three-wheel drive system of the V-ribbed belt resonates，the transmission system the noise has increased significantly.